Epstein-Barr Virus-associated Pulmonary Tumor: A Pediatric Case and Discussion of the Literature. Issue 7 (October 2021) - Lecoq, Nathalie; Godefroid, Nathalie; Berardis, Silvia; Froidure, Antoine; Poncelet, Alain; Goubau, Christophe
Abstract : Epstein-Barr virus-associated smooth pulmonary tumor is a rare condition that mostly affects immunosuppressed patients. This case describes a young boy with a history of kidney transplantation who presented recurrent pneumonia. Multiple endobronchial soft tissue tumors affecting both right and left bronchial tree were found and partially removed by bronchoscopy. Immunohistologic analysis demonstrated Epstein-Barr virus-associated smooth pulmonary tumor. Immunosuppressive therapy was changed from tacrolimus to sirolimus. A few months later, new right upper lobe and inferior left lobe tumors were found. Recurrent left lower lobe pneumonia prompted lobectomy. In the present case, complete resection and change of immunosuppressive treatment were effective.